PPARγ Agonists: Emergent Therapy in Endometriosis - Vallée, Alexandre (Pharmaceuticals (Basel), 2021)
Endometriosis is one of the major gynecological diseases of reproductive-age women. This disease is characterized by the presence of glands and stroma outside the uterine cavity. Several studies have shown the major role of inflammation, angiogenesis, adhesion and invasion, and apoptosis in endometriotic lesions. Nevertheless, the mechanisms underlying endometriotic mechanisms still remain unclear and therapies are not currently efficient. The introduction of new agents can be effective by improving the condition of patients. PPARγ ligands can directly modulate these pathways in endometriosis. However, data in humans remain low. Thus, the purpose of this review is to summarize the potential actions of PPARγ agonists in endometriosis by acting on inflammation, angiogenesis, invasion, adhesion, and apoptosis.